Value of EUS in early detection of pancreatic ductal adenocarcinomas in patients with intraductal papillary mucinous neoplasms - Kamata, Ken; Kitano, Masayuki; Kudo, Masatoshi; Sakamoto, Hiroki; Kadosaka, Kumpei; Miyata, Takeshi; Imai, Hajime; Maekawa, Kiyoshi; Chikugo, Takaaki; Kumano, Masashi; Hyodo, Tomoko; Murakami, Takamichi; Chiba, Yasutaka; Takeyama, Yoshifumi (Endoscopy, 2014)
Background and study aims: Pancreatic ductal adenocarcinomas (PDAC) sometimes arise in patients with intraductal papillary mucinous neoplasms (IPMNs). This study examined the incidence of PDACs concomitant to or derived from branch duct IPMNs. The usefulness of endoscopic ultrasonography (EUS) relative to other imaging methods for detecting these tumors was also assessed. Patients and methods: This retrospective study used data from clinical records and imaging studies that were collected prospectively. During 2001 – 2009, 167 consecutive patients with IPMNs underwent EUS, ultrasonography, computed tomography (CT), and magnetic resonance imaging (MRI). The 102 patients whose branch duct IPMNs lacked mural nodules/symptoms and thus did not qualify for resection were followed up by semiannual EUS and annual ultrasonography, CT, and MRI. The sensitivity and specificity with which the four modalities detected IPMN-derived and -concomitant PDACs at the first examination and throughout the study period were evaluated. The rate of PDAC development during follow-up was analyzed by the Kaplan–Meier method.Results: A total of 17 IPMN-derived and 11 IPMN-concomitant PDACs were diagnosed at the first examination. Lesions that did not qualify for resection or chemotherapy were followed up for a median of 42 months. Seven IPMN-concomitant PDACs and no IPMN-derived PDACs were detected during follow-up. The 3- and 5-year rates of IPMN-concomitant PDAC development were 4.0 % and 8.8 %, respectively. At the first examination, EUS was superior to other imaging modalities in terms of IPMN-derived and -concomitant PDAC detection. Throughout the study period, including follow-up, EUS was significantly better at detecting IPMN-concomitant PDACs than the other modalities.Conclusions: IPMN-concomitant PDACs are quite often found at diagnosis and during follow-up. EUS examination of the whole pancreas plays an important role in the management of IPMNs as it allows the early detection of these small invasive carcinomas.